Effects of an adhesive force of admixed particles on compressed packing fractions in a particle bed - Peukert, Wolfgang; Paul, Jonas; Koch, Thomas; Yoshida, Mikio; Sanagawa, Tomoya; Okano, Shun-ichiro; Oshitani, Jun; Yamamoto, Hiroaki; Gotoh, Kuniaki (Advanced Powder Technology, 2015)
One of the techniques for a reduction in particle cohesiveness is the admixing of nano-particles. However, the mechanism of cohesiveness reduction has not yet been clarified. In this study we focused on a compressed packing fraction as one of the values reflecting the cohesiveness and flowability in a compressed particle flow. In order to estimate the mechanism of the reduction, the effects of an adhesive force of admixed particles on the packing fraction were investigated experimentally. In the experiments, silica particles with 397 and 8 nm diameters were used as the main and the admixed particles, respectively. The surfaces of the admixed particles were modified chemically in order to vary their adhesive force with maintaining morphological and mechanical characteristics. At more than 2.0% mixing mass ratios, the decreasing rate with increasing the mass ratio in net difference value of packing fraction for modified admixed particles was smaller than that for the raw particles. A calculation of the packing fraction of the admixed particles in the voids of main particles revealed that difference of the decreasing rates could be attributed to the difference of cohesivenesses between raw and modified admixed particles. The maximum packing fraction achieved by the modified admixed particles was lower than that achieved by the raw admixed particles. However, when a mixture of main and admixed particles was packed by tapping, the packing fraction with modified admixed particles was higher than that with raw admixed particles. This implied that the adequate adhesive force of admixed particles is different by the applied compression force value.
Keywords: Admixture of nano-particles; Chemical surface modification; Compressed particle bed; Packing fraction